A rapid and sensitive UPLC-MS/MS method for the determination of flibanserin in rat plasma: application to a pharmacokinetic study - Long He; Wenting You; Sa Wang; Tian Jiang; Caiming Chen (BMC Chemistry, 2019)
Abstract Background In this work, we aim to develop and validate a fast, simple, and sensitive method for the quantitative determination of flibanserin and the exploration of its pharmacokinetics. Methods Ultra-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) was the method of choice for this investigation and carbamazepine was selected as an internal standard (IS). The plasma samples were processed by one-step protein precipitation using acetonitrile. The highly selective chromatographic separation of flibanserin and carbamazepine (IS) was realised using an Agilent RRHD Eclipse Plus C18 (2.1 × 50 mm, 1.8 µ) column with a gradient mobile phase consisting of 0.1% formic acid in water and acetonitrile. The analytes were detected using positive-ion electrospray ionization mass spectrometry via multiple reaction monitoring (MRM). The target fragment ions were m/z 391.3 → 161.3 for flibanserin and m/z 237.1 → 194 for carbamazepine (IS). The method was validated by linear calibration plots over the range of 100–120,000 ng/mL for flibanserin (R2 = 0.999) in rat plasma. Results The extraction recovery of flibanserin was in the range of 91.5–95.8%. The determined inter- and intra-day precision was below 12.0%, and the accuracy was from − 6.6 to 12.0%. No obvious matrix effect and astaticism was observed for flibanserin. The target analytes were long-lasting and stable in rat plasma for 12 h at room temperature, 48 h at 4 °C, 30 days at − 20 °C, as well as after three freeze–thaw cycles (from − 20 °C to room temperature). The proposed method has been fully validated and successfully applied to the pharmacokinetic study of flibanserin.